Fremdenverkehr in Hawaii - Entwicklung und Perspektiven - Kreisel, Werner (ERDKUNDE, 1980)
Tourism is today Hawaii’s most important industry. Not only is it the largest source of export income and of jobs generated, but is has the largest growth potentials of all of Hawaii’s major industries. Tourism has surpassed the sugar and pineapple industry in importance for the islands’ economy. While moderate increases are noted in visitors from the US-mainland, recent figures indicate strong increases in overseas travel to Hawaii,primarily from Japan. The rapid growth of this industry since the fifties caused a building boom which took place particularly in Waikiki. The result is a visitors’ agglomeration with a skyline of high-rise-structures - for some however it is a concrete jungle which creates alarm over traffic and pollution problems, increased crime-rate etc. Nevertheless, new tourism is expanding and new tourist areas are developing on the neighbouring islands: the Lahaina-Napili-coast and the Kihei-Maalaea area on the Island of Maui, Kailua-Kona on the Big Island (Hawaii) and the east-coast of the Island of Kauai. Since Hawaii’s economy is dependent on tourism, there is some concern that because this industry has been fickle in other parts of the world, it may be inherently unstable. In the event of a visitor industry recession, Hawaii could be subject to an economic collapse. However, there is no alternative to be seen for the future economic growth of the Islands.